2007
DOI: 10.1002/zaac.200700088
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Coordination Polymers with Amino Acids: $\rm ^{2}_{\infty}[Cu_{2}(\mu-L-tryptophanato)_{2}(\mu-4,4\prime-bipyridine)(H_{2}O)_{2}](NO_{3})_{2}$

Abstract: The two-dimensional mixed-ligand network catena-[(µ-4,4Ј-bipyridine)-bis(µ-L-tryptophanato-κ 3 N,O,OЈ)-diaqua-dicopper(II) dinitrate] is constructed through the bridging action of both the tridentate amino carboxylato and the bidentate 4,4Ј-bipyridine ligand. The enantiomeric L-tryptophanato ligand acts as an N,O chelate towards one copper atom and bridges through the 1189 second carboxylate oxygen atom to the adjacent copper ion. Stacking of the corrugated nets creates channels which are occupied by the hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(23 citation statements)
references
References 44 publications
1
22
0
Order By: Relevance
“…51 Two typical stable geometries of [Bmim + ÁCl À ]-Pd, a1 and a2 were shown in Fig. 55,56 The typical stable structures of [Bmim + ÁCl À ]-Pd 2 were also displayed in Fig. The geometric parameters showed that in a1, the Pd atom formed direct interactions with both the imidazolium ring and the Cl À ion.…”
Section: The Structure Of Free Ion Pairsmentioning
confidence: 97%
“…51 Two typical stable geometries of [Bmim + ÁCl À ]-Pd, a1 and a2 were shown in Fig. 55,56 The typical stable structures of [Bmim + ÁCl À ]-Pd 2 were also displayed in Fig. The geometric parameters showed that in a1, the Pd atom formed direct interactions with both the imidazolium ring and the Cl À ion.…”
Section: The Structure Of Free Ion Pairsmentioning
confidence: 97%
“…The frameworks were built from nickel nitrate, trimesic acid (H 3 btc) and 1,2-propanediole (pd) as co-ligand whose chirality is responsible for the sense of rotation of the network. By adding an auxiliary ligand, here 3-picoline (pic), they afforded a material, named Ni 3 (btc) 2 (pic) 6 (pd) 3 (30) with permanent microporosity (channel size > 1 nm). From nitrogen physisorption a Type I isotherm was observed typical for microporous materials, and a surface area of 930 m 2 g -1 could be calculated [59].…”
Section: Chiral Metal-organic Framework In Separationmentioning
confidence: 99%
“…Further, by using an organic linker with pyrimidine groups, Chen and co-workers prepared a porous MOCCs with high methane storage working capacity, which is attributed to the functional dynamic pyrimidine groups [26]. Meanwhile, the introduction of a second ligand in the MOCC systems has been proved to be very effective in enriching the structures of MOCCs [27][28][29][30][31]. Although such great progress has been achieved, the precise controllable synthesis of MOCCs with expected structures and properties is still a challenging work, because the construction of MOCCs is greatly influenced by the structure-directing factors including at least the temperature, solvent, metal ion, organic ligand, pH value of the solution, counter ion, and metal-to-ligand ratio [32][33][34].…”
Section: Introductionmentioning
confidence: 99%